MODELING ESTIMATION OF FINANCIAL SUSTAINABILITY OF MECHANISM OF FINANCING LEASING OPERATIONS - Левченко, Олександр (Socio-economic relations in the digital society, 2019)
The article proposes a logistic model for assessing the financial stability of the mechanism of financing leasing operations, identified the advantages and disadvantages of proposed model. Carried out the estimation of probability of default occurrence of the fund for financing leasing operations for increasing the ratio of financial leverage and taking into account the eff ect of a number of economic and fi nancial factors: the emergence of competitive forms of fi nancing of fixed capital and renewal of fixed assets, infl ationary risks, volatility of the exchange rate and worsening conditions in the future for obtaining state support for fi nancing leasing operations. Carried out the forecast of probability of occurrence of fi nancial instability of the fund of fi nancing of leasing operations.